2015
DOI: 10.1681/asn.2014050468
|View full text |Cite
|
Sign up to set email alerts
|

Role of Myeloid-Derived Suppressor Cells in Glucocorticoid-Mediated Amelioration of FSGS

Abstract: The mechanism by which glucocorticoids alleviate renal inflammatory disorders remains incompletely understood. Here, we report that the efficacy of glucocorticoids in ameliorating FSGS depends on the capacity to expand myeloid-derived suppressor cells (MDSCs). After glucocorticoid treatment, the frequency of CD11b and kidney also increased after glucocorticoid treatment. The induced MDSCs from glucocorticoid-treated mice strongly suppressed T cells, dendritic cells, and macrophages but induced regulatory T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 59 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…The mechanism by which glucocorticoids affect podocytes are poorly understood; these agents are known to have direct effects on cultured podocytes (132). Recently, it has been suggested that these agents can expand the population of myeloid-derived suppressor cells that downregulate T cell function (133). Reliable and validated biomarkers of steroid responsiveness would be valuable.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The mechanism by which glucocorticoids affect podocytes are poorly understood; these agents are known to have direct effects on cultured podocytes (132). Recently, it has been suggested that these agents can expand the population of myeloid-derived suppressor cells that downregulate T cell function (133). Reliable and validated biomarkers of steroid responsiveness would be valuable.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…57 One of the mechanisms through which GC inhibits inflammation is to induce expansion of myeloid-derived suppressor cells (MDSC), which in turn suppress other immune cells. 58 Expansion of MDSC is also observed in high-fat diet-fed conditions. 57 In addition to inhibiting inflammation, GC therapy causes unwanted side effects, such as liver steatosis and hyperglycemia.…”
Section: Role Of Atf3 In Hepatic Steatosismentioning
confidence: 96%
“…Glucocorticoids were introduced in the therapy for the podocytopathies largely based on empiric evidence of success, particularly for MCD. The responses to this therapy have been taken as evidence of support for an immune role in pathogenesis, and there is some evidence for this [4]. Also, dexamethasone has direct effects to podocyte phenotype in vitro, including increasing nephrin mRNA expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…There are at least 2 possibilities: these agents modulate immune functions and/or have a direct effect on podocytes. A recent report suggested that in FSGS and MC, glucocorticoid sensitivity is due to an expansion of the Cd11b + HLA-DR -CD14 -CD15 + cell population; these cells are immature myeloid-derived stem cells that can suppress T cell responses [4]. This would add glucocorticoid-sensitive FSGS and MCD to the list of inflammatory and autoimmune diseases in which myeloid-derived stem cells are believed to play a role, including type 1 diabetes, multiple sclerosis, and inflammatory bowel disease [5].…”
Section: Introductionmentioning
confidence: 99%